The burning - Castillo, Linda (New York : Minotaur Books, 2024)
"Chief of Police Kate Burkholder investigates a gruesome murder that reveals a little-known chapter of early Amish history in this next riveting installment of the bestselling series by Linda Castillo. Newlywed Chief of Police Kate Burkholder is awakened by an urgent midnight call summoning her to a suspicious fire in the woods. When she arrives at the scene, she discovers a charred body. According to the coroner, the deceased, an Amish man named Milan Swanz, was chained to a stake and burned alive. It is an appalling and eerily symbolic crime against an upstanding husband and father. Kate knows all too well that the Amish prefer to handle their problems without interference from the outside world, and no one will speak about the murdered man. From what she's able to piece together, Swanz led a deeply troubled life and had recently been excommunicated. But if that's the case, why are the Amish so reluctant to talk about him? Are they protecting the memory of one of their own? Or are they afraid of something they dare not share? When her own brother is implicated in the case, Kate finds herself not only at odds with the Amish, the world of which she was once a part, but also the English community and her counterparts in law enforcement. The investigation takes a violent turn when Kate's life is threatened by a mysterious stranger. To uncover the truth about the death of Milan Swanz, Kate must dive deep into the Anabaptist culture, peering into all the dark corners of its history, only to uncover a secret legacy that shatters everything she thought she knew about the Amish themselves-and her own roots"--
Keywords: Amish -- Fiction; Detective and mystery fiction; Novels